2021
DOI: 10.1186/s40359-021-00581-y
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol of a factorial trial ECHO: optimizing a group-based school intervention for children with emotional problems

Abstract: Background Youth mental health problems are a major public health concern. Anxiety and depression are among the most common psychological difficulties. The aim of this study is to evaluate an optimized version of a promising indicated group intervention for emotional problems. The program (EMOTION Coping Kids Managing Anxiety and Depression) targets school children 8–12 years with anxious and depressive symptoms and examines three factors. Factor 1 compares the standard EMOTION intervention del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The current study was a part of a larger trial of an indicated transdiagnostic preventive intervention, the ECHO study (http://clinicaltrials.gov NCT04263558; see Neumer et al., 2021). Children and parents at participating schools received oral and written information about the study, inviting children who experienced symptoms of anxiety or depression to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…The current study was a part of a larger trial of an indicated transdiagnostic preventive intervention, the ECHO study (http://clinicaltrials.gov NCT04263558; see Neumer et al., 2021). Children and parents at participating schools received oral and written information about the study, inviting children who experienced symptoms of anxiety or depression to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…In the current study, we examined self-reported level of anxiety and depression before and during the pandemic, and the responses to COVID specific questions and quality of life as reported by children aged 8–12 years participating in a preventive randomized factorial trial (for study information, see Neumer et al, 2021 ). The COVID specific questions were designed to gather information on how the child was dealing with the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment thus focuses on improving the function of these areas by applying skill-based behavioral strategies ( Wenzel, 2017 ). Multiple studies have incorporated CBT’s emphasis on reducing cognitive errors and strengthening positive behavior into their designs by, for example, using fictional storylines to help participants correct irrational thought patterns during reflective tasks, thereby improving patients’ depression conditions ( Stasiak et al, 2014 ; Topooco et al, 2019 ; Neumer et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%